Parents' Perception About Factors of Quality Education in Private Schools in Kakinada City, Andhra Pradesh - Burlakanti, Kuberudu; Nagendra Kumar, Jatla; Srinivas, Romala Vijaya (Prabandhan: Indian Journal of Management, 2015)
Education is the only way of enlightening the human life and man can only aspire for attaining perfection after attaining education. In the case of India, education has been in the boom stage in terms of promoting education in the most sophisticated and divergent ways. In the present scenario, competition is the only driving factor for students as well as parents, and they only think about the best place from where they can acquire the assured competency to win the race. Imparting education is merely the most prime concept for every educational institution in order to entice the parents. Indeed, private schools are persistently adapting new techniques of qualitative education in terms of well trained and highly qualified faculty, e-learning, empirical thinking techniques, good infrastructure, and so forth. Hence, the present study sheds light on the perception of parents whose children were enrolled in 20 best private schools in Kakinada city, Andhra Pradesh. We randomly chose 200 parents who were personally interviewed to ascertain their perceptions with regards to what are the important factors considered by them while choosing a school for their wards. In the present study, we used the statistical tools like factor analysis, Karl Pearson's correlation coefficient, and regression analysis to ascertain the most influential factors of quality education.